Power, Corruption and Dissent: Varieties of Contemporary Croatian Political Catholicism - Perica, Vjekoslav (Occasional papers on religion in Eastern Europe, 2015)
"Two decades after the major Balkan war in Croatia and Bosnia-Herzegovina 1991-1995, the dynamic of feuding ethnic nationalisms has shifted from the initially strongest Serbian to the currently dominant Croatian nationalism. The two strongest nationalisms of the (post)Yugoslav region are comparable to each other in many respects including the ethno-confessional nationalistic ideology amalgamated with religion and crucial roles for the churches as national institutions allied with nationalistic parties. The relative advantage for Croatian Catholicism is the outcome of several factors such as the following:..."